Incidence of pacing‐induced cardiomyopathy in pacemaker‐dependent patients is lower with leadless pacemakers compared to transvenous pacemakers. (25th November 2020) - Sanchez, Reynaldo; Nadkarni, Anish; Buck, Benjamin; Daoud, Georges; Koppert, Tanner; Okabe, Toshimasa; Houmsse, Mahmoud; Weiss, Raul; Augostini, Ralph; Hummel, John D.; Kalbfleisch, Steven; Daoud, Emile G.; et al.
Abstract: Introduction: Frequent right AQ4ventricular pacing (≥40%) with a transvenous pacemaker (TVP) is associated with the risk of pacing‐induced cardiomyopathy (PICM). Leadless pacemakers (LPs) have distinct physical and mechanical differences from TVP. The risk of PICM with LP is not known. To identify incidence, predictors, and long‐term outcomes of PICM in LP and TVP patients. Methods: The study comprised all pacemaker‐dependent patients with LP or TVP who had left ventricular ejection fraction (LVEF) of ≥50 from 2014 to 2019. The incidence of PICM (≥10% LVEF drop) was assessed with an echocardiogram. Predictors for PICM were identified using multivariate analysis. Long‐term outcomes after cardiac resynchronization (CRT) were assessed in both groups. Results: A total of 131 patients with TVP and 67 with LP comprised the study. All patients in the TVP group and the majority in the LP group underwent atrioventricular node ablation. The mean follow‐up duration in TVP and LP groups was 592 ± 549 and 817 ± 600 days, respectively. A total of 18 (13.7%) patients in TVP and 2 (3%) in LP developed PICM after a median duration of 254 (interquartile range: 470) days. The incidence of PICM was significantly higher with TVP compared with LP ( p = .02). TVP as pacing modality was a positive (odds ratio [OR]: 1.07) while age was negative (OR: 0.94) predictor for PICM on multivariable analysis. Both patients in LP and all except two in the TVP group responded to CRT. Conclusion: Incidence of PICM is significantly lower with LP compared with TVP in pacemaker‐dependent patients. Age and TVP as pacing modality were predictors for PICM.